The Effect of Investment Opportunity Set, Funding Decisions and Dividend Policy on Firm Value - Yuni Dwi Cahya; Dwi Septiani (Universitas Muhammadiyah Prof. DR HAMKA., 2024)
The impact of the Dividend Policy, Financing Decisions, and Investment Opportunity Set on Firm Value are investigated in this study. A quantitative strategy is used, with purposive sampling combined with secondary data analysis to choose the sample according to predetermined standards. The results show that the best model for this analysis is the Random Effect Model (REM). The findings also show that Firm Value is impacted by the Investment Opportunity Set, Financing Decisions, and Dividend Policy taken together. Moreover, Firm Value is influenced by the Investment Opportunity Set and Financing Decisions separately; Dividend Policy has no discernible impact.